Primary Cardiac Lymphoma Presenting with Thrombocytopenia, Right Heart Failure, and Cardiogenic Shock - Kurniawan, Samantha; Mathur, Gita; Bogun, Yvonne; Kidson-Gerber, Giselle (Case Reports in Hematology, 2023)
Primary cardiac lymphoma (PCL) is a rare, potentially fatal subtype of non-Hodgkin’s lymphoma. Thrombocytopenia has also infrequently been reported in association with other primary cardiac tumours and can add substantial morbidity to an already life-threatening diagnosis if present. We report a rare case of a 70-year-old man who presented with thrombocytopenia (91 × 109/L) and progressive right heart failure. Transthoracic echocardiogram revealed a large 8 × 4 cm right atrial mass with severe tricuspid obstruction, confirmed as PCL on subsequent endomyocardial biopsy and immunohistochemistry. He deteriorated into cardiogenic shock precipitated by atrial fibrillation, with worsening thrombocytopenia (18 × 109/L) in the setting of ischaemic hepatitis. The patient stabilised with initiation of high dose steroids prior to tissue diagnosis and platelet counts normalised following chemotherapy. This case demonstrates the importance of considering PCL as a diagnosis and preemptive initiation of high dose steroids to improve outcomes in PCL associated with cardiogenic shock. This case also elucidates a potential pathophysiological association between PCL and thrombocytopenia.